Inovasi Penggunaan Media Audio Visual Terhadap Hasil Belajar Siswa (Studi Kasus) di SDN Rancaekek 02 - Kartika, Ruliyatna; Purwanda, Eka (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to analyze the impact of innovative use of audio-visual media on student learning outcomes at SDN Rancaekek 02. A qualitative approach was used by collecting data through interviews with five teachers and the principal. The research results show that the use of audio-visual media, such as video and animation, contributes significantly to improving student learning outcomes. Students who learn with this media are more involved in the learning process and show a better understanding of the subject matter. In addition, young teachers who are more creative in using technology have succeeded in creating an interactive and interesting learning atmosphere, thereby increasing student motivation and achievement. However, challenges arise for senior teachers who have difficulty adapting to technology. Therefore, additional training is needed to maximize the potential of this innovation. This research emphasizes the importance of integrating technology in education to support better learning outcomes and be relevant to today's student needs.